Policy Analysis of Enforcement of Halal Product Guarantee Regulations Through The Regulatory Impact Analysis (RIA) Approach - Purwanto, Hery; Jati, Sumunar; Rofiq, Ahmad (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2021)
Halal products are products consumed by the community, especially Muslim communities. Given that Indonesia is a Muslim-majority country, the State handles the production and distribution of halal products. In 2019, the Ministry of Religion stipulated Regulation of the Minister of Religion of the Republic of Indonesia (PMA) Number 26 of 2019 concerning Guaranteed Halal Products. Therefore, enforcement of halal certification for products circulating in Indonesia is mandatory. However, regulation enforcement generally has many challenges to predict impacts without detailed studies and consultations with affected parties. In this regard, the purpose of this study is to analyze the impact of the application of PMA number 26 of 2019 compulsorily by using Regulatory Impact Analysis (RIA). This study concludes a gap between current conditions and ideal conditions that need to be postponed to enact the Regulation of the Minister of Religion of the Republic of Indonesia Number: 26 of 2019 by correcting the gap.